Patient-Reported Outcome Measures in the Food and Drug Administration Pilot Compendium: Meeting Today’s Standards for Patient Engagement in Development? - Oehrlein, Elisabeth M.; Perfetto, Eleanor M.; Love, T. Rose; Chung, Yujin; Ghafoori, Parima (Value in health, 2018)
In 2016, the Food and Drug Administration (FDA) released a Pilot Clinical Outcome Assessment Compendium (COA Compendium) intended to foster patient-focused drug development (PFDD). However, it is unclear whether patient perspectives were solicited during development or validation of the included patient-reported outcome (PRO) measures. To examine the pedigree of a sample of measures included in the COA Compendium. PROs included in chapters 1 or 2 of the COA Compendium were extracted and three reviewers independently searched PubMed and Google to identify information on measure pedigree. Data on method and stage of measure development where patient engagement took place were documented. Among the 26 evaluated PRO measures, we were unable to identify information on development or validation on nearly half the sample (n = 12). Among the remaining 14 measures, 5 did not include any evidence of patient engagement; 2 engaged patients during concept elicitation only; 1 engaged patients during psychometric validation only; and 6 engaged patients during both concept elicitation and cognitive interviewing. Measures either previously qualified or submitted for qualification were more likely to include patient engagement. For the FDA Pilot COA Compendium to fulfill its purpose of fostering PFDD, it needs fine-tuning to reflect today’s standards, improving transparency and facilitating clear identification of included measures so that the level of patient engagement, among other factors, can be properly assessed. Suggested improvements include identifying clinical trials that correspond to the COA Compendium’s use in drug development; more clearly identifying which measure is referred to; and including only those measures that already qualified or undergoing qualification.